Respostas

2013-12-03T15:45:29-02:00
A) X+ 4 = X - 6
    -----       ----
      7         2
2x + 8 = 7x - 42
----------    ----------
    14         14        
2x - 7x = - 42 - 8 
- 5x = - 50  (- 1 )
x = 10

B) X+3 = X+8
    -----     -----
      8        5
5x + 15 = 8x + 64
-----------    ------------
    40         40
 
5x - 8x = 64 - 15
- 3x = 49  (- 1)
x = 49 / 3


C) X+6 = X-4
    -----     ----
     9        5
5x + 30 = 9x -36
-----------    -----------
  45             45
5x - 9x = - 36 - 30
- 4x = - 66 ( - 1)
x = 16.5 ou 33 / 2


D) X+3 = X-8
    -----     ----
      6        3
2x + 6 = 4x - 32
---------     ---------
 12           12
2x - 4x = - 32 - 6
- 2x = - 38   (- 1)
x = 19

E) X+4 = X-6
    -----     ----
     5        2
2x + 8 = 5x - 30
---------    ---------
   10        10 
2x - 5x = - 30 - 8 
- 3x = - 38 (- 1)
x = 38 / 3 

F) X+6 = X-8
    -----     ----
     7        4

4x + 24 = 7x - 56
----------     ----------
  28            28
4x - 7x = - 56 - 24
- 3x = - 80 (- 1)
x = 80 / 3